Locust Lane - Amidon, Stephen (Celadon Books, 2023)
"When three teenagers--Hannah, a sweet girl with an unstable history; Jack, the popular kid with a mean streak; and Christopher, an outsider desperate to fit in--become suspects in the murder of a fellow student, their parents will do anything to protect them, even at the others' expense"--